The alchemy of coaching: psychological capital as HERO within coaches’ selves - Burhanuddin, Nur Aimi Nasuha; Ahmad, Nor Aniza; Said, Rozita @ Radhiah; Asimiran, Soaib (Multidisciplinary Digital Publishing Institute, 2022)
The complex nature of coaching challenges instructional coaches (ICs) professionally as it requires them to deal with not only teachers’ resistance, acceptance and expectation but also adhere to the complex and multifaceted roles that they are bearing. Psychological capital (PsyCap) has been upheld as an effective construct for defending against stress, negative emotions and burnout among educators. This phenomenological study explores ways in which PsyCap was experienced by Malaysian instructional coaches (ICs). Data were gathered from face-to-face interviews with seven instructional coaches purposefully selected from six different District Education Offices (DEOs) throughout Malaysia. Extracted from participants’ own words and through the exploration performed, PsyCap was experienced by the participants through a sense of responsibility, positive resources and work commitment. This study highlights the importance of PsyCap as inner positive psychological resources that aided instructional coaches in their practice of coaching. In addition, this study suggests future research recommendations towards implementing PsyCap developmental training with another group of instructional coaches.